A Chemical-Induced, Seed-Soaking Activation Procedure for Regulated Gene Expression in Rice - Chen, Zaijie; Cheng, Qianqian; Hu, Chanquan; Guo, Xinrui; Chen, Ziqiang; Lin, Yan; Hu, Taijiao; Bellizzi, Maria; Lu, Guodong; Wang, Guo-Liang; Wang, Zonghua; Chen, Songbiao; et al. (Frontiers in Plant Science, 2017)
Inducible gene expression has emerged as a powerful tool for plant functional genomics. The estrogen receptor-based, chemical-inducible system XVE has been used in many plant species, but the limited systemic movement of inducer β-estradiol in transgenic rice plants has prohibited a wide use of the XVE system in this important food crop. Here, we constructed an improved chemical-regulated, site-specific recombination system by employing the XVE transactivator in combination with a Cre/loxP-FRT system, and optimized a seed-soaking procedure for XVE induction in rice. By using a gus gene and an hpRNAi cassette targeted for OsPDS as reporters, we demonstrated that soaking transgenic seeds with estradiol solution could induce highly efficient site-specific recombination in germinating embryos, resulting in constitutive and high-level expression of target gene or RNAi cassette in intact rice plants from induced seeds. The strategy reported here thereby provides a useful gene activation approach for effectively regulating gene expression in rice.